2012
DOI: 10.1152/ajpgi.00430.2011
|View full text |Cite
|
Sign up to set email alerts
|

RhoA/ROCK pathway is the major molecular determinant of basal tone in intact human internal anal sphincter

Abstract: Rattan S, Singh J. RhoA/ROCK pathway is the major molecular determinant of basal tone in intact human internal anal sphincter. Am J Physiol Gastrointest Liver Physiol 302: G664 -G675, 2012. First published January 12, 2012; doi:10.1152/ajpgi.00430.2011.-The knowledge of molecular control mechanisms underlying the basal tone in the intact human internal anal sphincter (IAS) is critical for the pathophysiology and rational therapy for a number of debilitating rectoanal motility disorders. We determined the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
45
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 39 publications
5
45
2
Order By: Relevance
“…93,94 ROCK and MYPT1 phosphorylation contribute substantially to the constitutive tonic contracted state of the IAS. 95 ROCK inhibition decreases the basal tone, and reduces the phosphorylation levels of MYPT1 T697, CPI-17 T38, and MLC S19 in rat IAS smooth muscles. 48,95 With human IAS smooth muscles, it has been reported that PKC inhibitors significantly decrease T38 phosphorylation, with modest effects on IAS smooth muscle tone, while ROCK inhibition produces significantly greater relaxation of IAS smooth muscle cells than PKC inhibition.…”
Section: Inhibition Of Myosin Light Chain Phosphatase Activity By Mypmentioning
confidence: 86%
See 1 more Smart Citation
“…93,94 ROCK and MYPT1 phosphorylation contribute substantially to the constitutive tonic contracted state of the IAS. 95 ROCK inhibition decreases the basal tone, and reduces the phosphorylation levels of MYPT1 T697, CPI-17 T38, and MLC S19 in rat IAS smooth muscles. 48,95 With human IAS smooth muscles, it has been reported that PKC inhibitors significantly decrease T38 phosphorylation, with modest effects on IAS smooth muscle tone, while ROCK inhibition produces significantly greater relaxation of IAS smooth muscle cells than PKC inhibition.…”
Section: Inhibition Of Myosin Light Chain Phosphatase Activity By Mypmentioning
confidence: 86%
“…48,95 With human IAS smooth muscles, it has been reported that PKC inhibitors significantly decrease T38 phosphorylation, with modest effects on IAS smooth muscle tone, while ROCK inhibition produces significantly greater relaxation of IAS smooth muscle cells than PKC inhibition. 95,96 However, it has also been reported that the PKC activator PDBu relaxes opossum IAS. 97 A variety of non-cholinergic agonists have been reported to increase CPI-17 and MYPT1 phosphorylation and activate myofilament Ca 2+ sensitization.…”
Section: Inhibition Of Myosin Light Chain Phosphatase Activity By Mypmentioning
confidence: 99%
“…Recently, significant data in intact IAS of humans and animals demonstrated that the predominant molecular regulatory mechanism for IAS tone is the RhoA/ROCK pathway over the PKC pathway (26, 30, 32). However, little is known about the patterns of rectal smooth muscle (RSM) contractions and regulatory mechanisms of the RSM, especially in the basal state.A good starting point would be analysis of the contractile patterns in the phasic activity in the RSM in the basal state (29,30,32). In the gastrointestinal tract smooth muscle, spontaneous contractions vary from 3 min Ϫ1 (in the stomach) to 8 -12 min Ϫ1 (in the small and large intestine) (33).…”
mentioning
confidence: 99%
“…These factors are impairment of basal internal anal sphincter (IAS) tone and external anal sphincter, puborectalis, and colorectal smooth muscle compliance. Recently, significant data in intact IAS of humans and animals demonstrated that the predominant molecular regulatory mechanism for IAS tone is the RhoA/ROCK pathway over the PKC pathway (26,30,32). However, little is known about the patterns of rectal smooth muscle (RSM) contractions and regulatory mechanisms of the RSM, especially in the basal state.…”
mentioning
confidence: 99%
See 1 more Smart Citation